Algorithm Policy for the Authentication of Indirect Fingerprints Used in Cloud Computing - Bodepudi, Anusha; Reddy, Manjunath; Gutlapalli, Sai Srujan; Mandapuram, Mounika (American Journal of Trade and Policy, 2021)
User identity identification secures cloud computing. This study examined cloud service security authentication needs. Fingerprint recognition was used to create a new cloud security authentication system. The proposed system’s design and process were thoroughly examined to secure cloud user data from unauthorized access. This study proposes a secure cloud server fingerprint match technique. Considering fingerprint uniqueness and stability, cloud security login authentication technology employing fingerprint recognition is researched to improve cloud services login security. Analyze the cloud security login system structure first. Next, fingerprint identification is explained. Finally, fingerprint identification of cloud security login systems is investigated from fingerprint registration, certification, fingerprint image processing perspectives, and a simple fingerprint image processing simulation. The results show that this login mechanism is secure and versatile. The biometric template is insecure, and stolen templates cannot be canceled, making user identity leaks easy. This work proposes indirect fingerprint authentication to address these issues. Finally, a thorough security analysis of the cloud computing method is offered.